ANALISIS MISKONSEPSI PESERTA DIDIK KELAS VI SEKOLAH DASAR PADA MATERI TATA SURYA MELALUI INSTRUMEN THREE TIER - Basuki, Aris; Fakhriyah, Fina; Sulistyorini, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to analyze the misconceptions experienced by six grade elementary school students on the Solar System material using the Three tier test instrument. This research was conducted at SDN VI Ngabul in July 2025. This research method is descriptive quantitative with a diagnostic test method. The number of samples used was 10 fifth grade students. The misconception instrument used to measure elementary school students' misconceptions is using a three-tier test format (Three tier Test). The researcher used an instrument in the form of a test with a level of confidence. The first level is the choice of answers to the questions asked, the second level contains the level of confidence in the answers that have been chosen, the third level presents the reasons for choosing the answer. Based on the results and discussion of the study, it can be concluded that the misconceptions of six grade elementary school students regarding the Solar System material are still quite high, especially in the concept of planetary order, direction of rotation, and planetary classification. Misconceptions do not only occur due to lack of understanding, but also because students believe in wrong concepts, which are obtained from various sources such as preconceptions, media, teacher teaching methods, and textbooks. The use of the three-tier test instrument is very effective in revealing students' understanding, level of confidence, and reasons, so that it can be the basis for evaluating learning. To overcome misconceptions, the mindscaping learning model is recommended as an effective method because it can help students visualize and reconstruct concepts more clearly and meaningfully.